Argentina : Macroeconomic Crisis and Household Vulnerability - Inchauste, Gabriela (IMF Working Papers; Working Paper ;, 2003)
Using urban household surveys, we constructed a panel dataset to study the effects of the Argentine macroeconomic crisis of 1999-2002 with the aim of (1) identifying the most vulnerable households, (2) investigating whether employment in the public sector and government spending served to decrease vulnerability, and (3) understanding the mechanisms used by households to smooth the effects of the crisis. Households whose heads were male, less educated, and employed in the construction sector were more vulnerable to the crisis, experiencing larger-than-average declines in income and higher dispersion. Households whose heads were employed in the public sector were more protected from the crisis, although higher public spending did not serve to decrease their vulnerability. A significant source of vulnerability was linked to changes in employment status, and we studied the determinants of the probability of being unemployed and of becoming unemployed. Last, we found that households were unable to perfectly smooth income shocks. Given these results, there is room for broadening social safety nets, particularly in the form of public works programs.